The impact of self-control on aggressive behavior: the chained mediating role of hostile attribution bias and positive/negative implicit affect - Ma, Qiannan; Wang, Xiaoyin; Liu, Lanxi (Frontiers in Psychology, 2025)
ObjectiveThis study examined the direct impact of self-control on aggressive behavior and the mediating roles of hostile attribution bias and both positive and negative implicit affect.MethodsA questionnaire survey was conducted among 545 vocational students at a vocational school in Henan Province, utilizing the Self-Control Scale, Hostile Attribution Bias Questionnaire, Implicit Positive–Negative Affect Test, and Aggressiveness Behavior Scale as measurement tools. Data were analyzed using SPSS 26.0 and PROCESS 4.1.ResultsThe findings revealed that selfcontrol negatively correlated with aggressive behavior, negative implicit affect, and hostile attribution bias, but showed a positive correlation with positive implicit affect. A significant chained mediating effect of hostile attribution bias and negative implicit affect was observed, while the mediating effect of positive implicit affect was not significant.DiscussionThese results confirm that self-control influences aggressive behavior through a complex psychological pathway, highlighting the critical roles of hostile attribution bias and negative implicit affect in this process. The findings provide a basis for interventions targeting aggressive behavior based on psychological variables.